Perceived effectiveness of telehealth services among adult patients with healthcare needs in a highly urbanized city - Vargas, Ave Marie; Arnibal, Sheila (Technium Social Sciences Journal, 2024)
Telehealth services are essential optional tools for therapy and potential strategies in providing healthcare regardless of the patient-doctor face to face meeting. Hence, this study determined the perceived effectiveness of the telehealth services in terms of patient receiving care, collaborative intervention, nurturing patients, and cost as assessed by adult outpatients with healthcare needs in private clinics in Bacolod City, Philippines relative to sex, age, and case. Also, it identified their challenges in availing the telehealth services. Likewise, it investigated the difference in the telehealth services’ perceived effectiveness when grouped to the demographics. Using the descriptive-comparative design, a validated and reliability tested questionnaire was responded by 158 adult patients. In analysis, it utilized mean, standard deviation, percentage distribution, rank, and Mann Whitney U test. Meanwhile, the researcher adhered to the Philippine Health Research Ethics Board. Generally, the perceived effectiveness of telehealth services was rated very high. All areas were also scored very high along with all the demographics. Meanwhile, they were mostly challenged virtually in terms of poor internet connectivity, lessening of proper evaluation, and hindering of quality patient assessment. Inferentially, there was no difference in the perceived effectiveness when grouped to all demographics. Hence, the findings imply the continuous utilization of the telehealth services in effectively providing the patients with quality healthcare.